2015
DOI: 10.1007/s11136-015-0955-1
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis on pain treatment satisfaction among Chinese patients with chronic pain: predictors and association with medical adherence, disability, and quality of life

Abstract: Distinct trajectories in pain treatment satisfaction were displayed in the current sample of Chinese patients with different disability grading chronic pain. Within pain treatment, only medication characteristics significantly impacted patients' medical adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
3
22
1
4
Order By: Relevance
“…As hypothesized, the associations between satisfaction with treatment process attributes and adherence were statistically significant and slightly larger than the associations between satisfaction with treatment process attributes and perceived insomnia severity at post‐test; compared to satisfaction with process attributes, satisfaction with outcome attributes was more highly associated with perceived insomnia severity at post‐test. These findings are comparable to those reported by others (Barbosa et al, ; Fontana et al, ; George & Robinson, ; Smith et al, ; Wong et al, ) and support the construct validity of the MDTSM subscales.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As hypothesized, the associations between satisfaction with treatment process attributes and adherence were statistically significant and slightly larger than the associations between satisfaction with treatment process attributes and perceived insomnia severity at post‐test; compared to satisfaction with process attributes, satisfaction with outcome attributes was more highly associated with perceived insomnia severity at post‐test. These findings are comparable to those reported by others (Barbosa et al, ; Fontana et al, ; George & Robinson, ; Smith et al, ; Wong et al, ) and support the construct validity of the MDTSM subscales.…”
Section: Discussionsupporting
confidence: 90%
“…Construct validity was determined by examining if the items comprising a subscale loaded on one factor reflecting the respective treatment attribute and investigating the association of the MDTSM subscales with two conceptually related variables—treatment adherence and treatment outcome (e.g., Peyrot & Rubin, ; Rejas et al, ; Schulte et al, ; Tierney & Kane, ). Specifically, it was hypothesized that satisfaction with treatment process attributes would be more highly correlated with adherence, whereas satisfaction with treatment outcome attributes would be more highly associated with the outcome (i.e., perceived insomnia severity) measured at post‐test, as implied by recent findings (Barbosa et al, ; Fontana et al, ; George & Robinson, ; Kendra et al, ; Smith et al, ; Wong et al, ).…”
Section: Multi‐dimensional Treatment Satisfaction Measurementioning
confidence: 99%
“…Wong et al 30 reported that baseline kinesiophobia significantly predicted positive changes in pain severity at 6 months, even when adjusted for sociodemographic factors and pain variables (number, duration and intensity). Van den Houte et al 32 did not report the predictive value of kinesiophobia on pain severity.…”
Section: Resultsmentioning
confidence: 99%
“…Wong et al 30 reported that greater degree of kinesiophobia at baseline significantly predicted lower levels of quality of life at 6 months, even after being adjusted for sociodemographic factors and pain variables (number, duration and intensity). However, the relationship was only significant with respect to physical function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation